(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
This scientific article delves into the intricate interplay between psychology and literature through an examination of the poetic works of Anna Akhmatova, a prominent Russian poet of the 20th century. Akhmatova’s poetry is celebrated for its profound emotional depth and intricate psychological insights. This article aims to analyze the psychologism inherent in Akhmatova’s lyrical compositions, exploring how her poetic expressions provide a window into the human psyche and its complex emotions. By examining select poems, stylistic devices, and recurring themes, we uncover the ways in which Akhmatova masterfully conveys psychological nuances, making her poetry a captivating exploration of the human condition.